PENDAMPINGAN PEMBUATAN ALAT PERMAINAN TRADISIONAL SEBAGAI UPAYA PELESTARIAN BUDAYA DAN INOVASI MEDIA PEMBELAJARAN PADA MAHASISWA PGSD - Naheria, Naheria; Cahyaningrum, Gyta Krisdiana; Cahyono, Didik; Fauzi, Muhammad Sukron (Gapenas Publisher, 2025)
Traditional games played using tools have important value both in the context of education and cultural preservation. This game tool functions as a concrete medium that is able to enrich the student learning experience. This Community Service activity aims to assist students of the Elementary School Teacher Education Study Program (PGSD) in designing and making traditional game tools. The activity was carried out through technical assistance and simulation of the use of game tools made by students. Based on the evaluation results, it was found that 54.2% of students demonstrated a very good understanding of the concept of traditional games, while 45.8% showed a sufficient understanding. In terms of developing ideas and creativity, 60% of students felt very helped and 40% felt quite helped in developing creative ideas for making game tools. Providing new experiences for students, especially in the process of designing and creating learning media based on regional games, 65.5% of students felt that they got a new experience, and 33.5% felt that it was enough to get a new experience. The feasibility of the traditional game tools produced, as many as 41.3% of students stated that the tools were quite applicable in learning in elementary school, and 58.7% considered that the tools were very applicable in the context of thematic learning at the elementary school level. These findings show that mentoring activities can encourage increased understanding, creativity, and practical competence of PGSD students as prospective educators who are innovative and culturally insightful